BOOK REVIEW: T.V. REED, "THE BLOOMSBURY INTRODUCTION TO POSTMODERN REALIST FICTION: RESISTING MASTER NARRATIVES", NEW YORK: BLOOMSBURY, 2021, 274 P. - Laura WALKER SAVU (Studia Universitatis Babeş-Bolyai. Philologia, 2022)
T.V. Reed, the Lewis E. and Stella G. Buchanan Distinguished Professor of English and American Studies at Washington State University, opens his wide-ranging survey of “postmodern realist fiction” with an intriguing statement: “There is no such thing as postmodern fiction.” This is because postmodernism is “not one agreed-upon thing” (15), but rather “a notoriously slippery category,” “a global phenomenon, with writers hailing from all continents,” except for Antarctica (1), and according to its first major theorist, Jean-François Lyotard, “a recurring historical phenomenon,” arising “whenever segments of a culture develop an intense self-consciousness about language as a force in creating the world” (5). Both the origins and endpoints of postmodernism have been intensely debated, while the lines separating it from other forms of representation have been drawn and redrawn in ways that allow for but are not limited to what Reed calls postmodernist realism: a body of late twentieth-century and early twenty-first-century works that “while still critical of ‘realism’ as a conservative ideology, tend to retain more recognizable elements of traditional fiction” (12), along with the imprint of their social and historical locations. As such, these narratives stand in sharp contrast to, on the one hand, “distorted versions of postmodernism” that have been dismissed as “empty formalism” (10), as “obscure and cynical worldplay, lacking both substance and moral values” (2, 3), and, on the other, to “white supremacist, misogynist, anti-immigrant, anti-Semitic, and Islamophobic discourses” that have been on the rise in the last decade or so (2-3).